Epithelial chemokine CXCL14 synergizes with CXCL12 via allosteric modulation of CXCR4. Issue 7 (30th March 2017) - Collins, Paul J.; McCully, Michelle L.; Martínez‐Muñoz, Laura; Santiago, César; Wheeldon, James; Caucheteux, Stephan; Thelen, Sylvia; Cecchinato, Valentina; Laufer, Julia M.; Purvanov, Vladimir; Monneau, Yoan R.; Lortat‐Jacob, Hugues; et al.
ABSTRACT: The chemokine receptor, CXC chemokine receptor 4 (CXCR4), is selective for CXC chemokine ligand 12 (CXCL12), is broadly expressed in blood and tissue cells, and is essential during embryogenesis and hematopoiesis. CXCL14 is a homeostatic chemokine with unknown receptor selectivity and preferential expression in peripheral tissues. Here, we demonstrate that CXCL14 synergized with CXCL12 in the induction of chemokine responses in primary human lymphoid cells and cell lines that express CXCR4. Combining subactive concentrations of CXCL12 with 100–300 nM CXCL14 resulted in chemotaxis responses that exceeded maximal responses that were obtained with CXCL12 alone. CXCL14 did not activate CXCR4‐expressing cells ( i.e., failed to trigger chemotaxis and Ca 2+ mobilization, as well as signaling via ERK1/2 and the small GTPase Rac1); however, CXCL14 bound to CXCR4 with high affinity, induced redistribution of cell‐surface CXCR4, and enhanced HIV‐1 infection by >3‐fold. We postulate that CXCL14 is a positive allosteric modulator of CXCR4 that enhances the potency of CXCR4 ligands. Our findings provide new insights that will inform the development of novel therapeutics that target CXCR4 in a range of diseases, including cancer, autoimmunity, and HIV.—Collins, P. J., McCully, M. L., Martínez‐Muñoz, L., Santiago, C., Wheeldon, J., Caucheteux, S., Thelen, S., Cecchinato, V., Laufer, J. M., Purvanov, V., Monneau, Y. R., Lortat‐Jacob, H., Legler, D. F., Uguccioni, M., Thelen, M., Piguet, V., Mellado, M., Moser, B. Epithelial chemokine CXCL14 synergizes with CXCL12 via allosteric modulation of CXCR4. FASEB J. 31, 3084–3097 (2017). www.fasebj.org